Comparative Effects of Triflusal, S-Adenosylmethionine, and Dextromethorphan over Intestinal Ischemia/Reperfusion Injury - Camara Lemarroy, Carlos Rodrigo; Guzmán de la Garza, Francisco Javier; Cordero Pérez, Paula; Alarcón Galván, Gabriela; Torres González, Liliana; Muñoz Espinosa, Linda Elsa; Fernández Garza, Nancy Esthela (2011)
Ischemia/reperfusion (I/R) is a condition that stimulates an intense inflammatory response. No ideal treatment exists. Triflusal is an antiplatelet salicylate derivative with anti-inflammatory effects. S-adenosylmethionine is a metabolic precursor for glutathione, an endogenous antioxidant. Dextromethorphan is a low-affinity N-methyl-D-aspartate receptor inhibitor. There is evidence that these agents modulate some of the pathways involved in I/R physiopathology. Intestinal I/R was induced in rats by clamping the superior mesenteric artery for 60 minutes, followed by 60 minutes of reperfusion. Rats either received saline or the drugs studied. At the end of the procedure, serum concentrations of tumor necrosis factor-alpha (TNF-alpha), malonaldehyde (MDA), and total antioxidant capacity (TAC) were determined and intestinal morphology analyzed. I/R resulted in tissue damage, serum TNF-alpha and MDA elevations, and depletion of TAC. All drugs showed tissue protection. Only triflusal reduced TNF-alpha levels. All drugs lowered MDA levels, but only triflusal and S-adenosylmethionine maintained the serum TAC.